2010
DOI: 10.1111/j.1748-1716.2010.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol on action potential and ionic membrane currents in rat ventricular myocytes

Abstract: Our results suggest a slight inhibition of all the currents at ethanol concentrations relevant to deep alcohol intoxication. The concentration dependence measured over a wide range may serve as a guideline when using ethanol as a solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…Thus, it seems to be the most suitable solvent to dissolve the hydrophobic compounds in such ells. Ethanol is also used as a solvent for hydrophobic compounds in experimental studies (28). Previous studies demonstrated that ethanol modulates the cell growth and suppresses cell proliferation dose dependently (29).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems to be the most suitable solvent to dissolve the hydrophobic compounds in such ells. Ethanol is also used as a solvent for hydrophobic compounds in experimental studies (28). Previous studies demonstrated that ethanol modulates the cell growth and suppresses cell proliferation dose dependently (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we updated our recently published model of the rat ventricular cardiomyocyte [37] to include characteristics of membrane currents measured in our recent experiments [2,3]. Using this model, we performed simulations allowing to predict the effect of ethanol on AP, SR Ca 2+ load, and intracellular Ca 2+ transient in rat ventricular cells.…”
mentioning
confidence: 97%
“…To obtain at least a rough estimate of the effects of ethanol on AP and Ca 2+ transient in human ventricular cells, we tentatively incorporated the known concentration dependences of ethanol-induced changes in ionic current components evaluated from the available experimental data [2,3,21,36] into a model of the human ventricular cardiomyocyte [13].…”
mentioning
confidence: 99%
“…The final tested concentrations were obtained by subsequent dilution in saline solution. The final dose of ethanol was 5m M which was proved not to affect ion currents on the membrane of cardiomyocyte (Bébarová et al 2010).…”
Section: Experimental Groupsmentioning
confidence: 99%